GRIT AND SOCIAL SUPPORT AS THE MODALITY OF SALES PROMOTER JOB PERFORMANCE - Maharani, Farah Diba; Hasanati, Nida; Mashuri, Muhammad Fath (Faculty of Psychology, Universitas Diponegoro, 2022)
Sales promoters have an essential role in achieving the company’s profit. Therefore, they are required to have a good performance. However, they often encounter various difficulties during their job performance that decrease employee performance. In overcoming this issue, grit exists in each individual, and social support from the sales promoter’s environment can help them increase their job performance. This research objective is to examine the influence of grit and social support on the job performance of sales promoters. The sampling technique used is simple random sampling. The sample of this research is a group of 180 sales promoters consisting of 132 men and 48 women with an age range of 20-40 years (M = 2.54; SD = 1.027). The instruments used in this study were the Job Performance Scale (24 items, α = .856), Grit Scale (20 items, α = .604), and Social Support Scale (30 items, α = .877). The analysis test by the multiple linear regression with the hypothesis testing t-test statistic showed a positive and statistically significant influence of grit and social support on the sales promoter job performance, adjusted R 2 = .608; F(2, 177) = 140.057, p < .001.